Media Sosial sebagai Sarana Pendidikan Politik oleh Pejabat Publik (Studi pada Akun Media Sosial Nur Hidayat Sardini) - Eri Nofianto; Fitriyah Fitriyah; Supratiwi Supratiwi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Social media plays an important role as a means of education, including as a means of political education. The use of social media as a means of political education is not only carried out by educational institutions, the media and the government, but also personally by actors within the government, including public officials. The development of digital technology today is a means for effective channeling of opinions and ideas, even digitizing information, one of which is through social media, which can affect the development of democracy. In the socio-political context, massive communication in cyberspace is currently able to influence the understanding and political awareness of citizens to their political preferences, so it is not surprising that many public figures use social media from just providing political education to campaigning, including those who become public officials. such as Nur Hidayat Sardini who uses social media as a means of educating electoral politics. This paper aims to analyze the extent to which the role of Nur Hidayat Sardini's social media can be useful in providing electoral political education to his audience. This paper is the result of a short research using digital ethnography as a research method. Supporting data comes from online news research journal articles, and social media analysis. The results showed that Nur Hidayat Sardini as a public official in the circle of election organizers seemed to have consistently contributed in the field of political education, especially in discussions related to electoral politics, the content presented was also technically communicative and easily digested by the audience, as an assessment of his social media accounts. can also be used as a reference for general public education materials.